A randomized controlled trial with a delayed‐type hypersensitivity model using keyhole limpet haemocyanin to evaluate adaptive immune responses in man. Issue 4 (28th October 2020) - Saghari, Mahdi; Gal, Pim; Ziagkos, Dimitrios; Burggraaf, Jacobus; Powell, John F.; Brennan, Nuala; Rissmann, Robert; van Doorn, Martijn B.A.; Moerland, Matthijs
Abstract : Aims: Keyhole limpet haemocyanin (KLH) immunization is a clinical model for the evaluation of human antibody responses. The current study evaluated the anti‐KLH antibody response after KLH immunization and the delayed‐type hypersensitivity response following intradermal KLH administration, using objective imaging techniques. Methods: Healthy male subjects aged 24.5 ± 5.4 years were randomized to intramuscular immunization with 100 μg KLH ( n = 12) or placebo ( n = 3). Anti‐KLH antibody (Ig) M and IgG titres were determined before and every 7 days after KLH immunization for a total of 28 days. Twenty‐one days after the immunization, all subjects received 1 μg KLH intradermally. Prior to and 2 days after intradermal KLH administration, skin blood perfusion, erythema and oedema were quantified using noninvasive imaging tools. Repeated measures ANCOVAs were used to analyse data. Results: Anti‐KLH IgM and IgG titres increased after KLH immunization compared to placebo (estimated difference [ED]: 37%, 95% confidence interval [CI]: 19–51% and ED: 68%, 95% CI: 56–76% respectively). Upon intradermal KLH administration an increase in skin blood perfusion (ED: 10.9 arbitrary units (AU), 95% CI: 1.4–20.4 AU) and erythema (ED: 0.3 AU, 95% CI: 0.1–0.5 AU) was observed in KLH‐immunized subjects compared to placebo. Conclusion: KLH immunization followed by intradermal KLH administration resulted in increased anti‐KLH IgM and IgG titres and a delayed‐type hypersensitivity response quantified by an increase in skin blood perfusion and erythema. Using noninvasive imaging tools the KLH model has the potential to serve as an objective tool to study the pharmacodynamics of T‐cell‐directed immunomodulatory drugs.